ANALYSIS OF TRANSPARENCY, ACCOUNTABILITY AND ROLE OF VILLAGE OFFICIALS IN VILLAGE FINANCIAL MANAGEMENT (CASE STUDY IN WANASARI DISTRICT, BREBES REGENCY) - Fora Susanti; Roni Roni; Yenny Ernitawati (Jurnal Ekonomi, 2023)
The village government is required to prepare the implementation report of the Village Budget Plan (APBDes) and be accountable for its outcomes. The village government is responsible for providing quality services, improving welfare, and promoting strategic regional development. Transparency can be achieved by providing easily accessible financial reports to the public through online and print media. Enhancing accountability and public trust in village financial performance is an important issue. However, the level of accountability in village financial management remains low and can lead to administrative failures, poor policy decisions and corruption. The allocation of village funds plays a significant role in advancing remote rural areas through infrastructure development and improving community welfare. The allocation of village funds is also important for developing local potentials and empowering marginalized rural communities. The objective of this research is to identify and analyze the influence of Transparency, Accountability, and the Role of Village Apparatus either individually or collectively on village financial management. The study will analyze village apparatus concerning the impact of transparency, accountability, and their role on village financial management in Wanasari Sub-District, Brebes Regency. The researcher will employ an associative causal method to determine the relationship between independent and dependent variables. Based on the results of the t-test and F-test analysis, it was found that Transparency, Accountability, and the Role of Village Apparatus significantly and independently influence village financial management. Further research is recommended to delve deeper into this study by incorporating relevant independent variables to broaden understanding of village financial management.